2022
DOI: 10.1111/jav.02984
|View full text |Cite
|
Sign up to set email alerts
|

Productivity drives the dynamics of a red kite source population that depends on immigration

Abstract: Local population dynamics are driven by local processes such as temporal variation of productivity, survival, emigration and population stage structure, and by processes originating from outside the local population, such as immigration. Populations may operate as sources that contribute more individuals than have died or as sinks that depend on neighbouring populations. Knowing demographic processes driving the dynamics of a local population and the significance of a local population in a system of multiple p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 77 publications
1
8
0
Order By: Relevance
“…Our estimate of juvenile survival (0.66) was within the higher range of juvenile survival observed for other medium‐sized raptors, such as the red kite Milvus milvus (mean = 0.55, min = 0.37, max = 0.80, Sergio et al 2021, Pfeiffer and Schaub 2023). In contrast, adult survival (0.71) appeared to be lower than expected based on an allometric relationship (Newton et al 2016).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our estimate of juvenile survival (0.66) was within the higher range of juvenile survival observed for other medium‐sized raptors, such as the red kite Milvus milvus (mean = 0.55, min = 0.37, max = 0.80, Sergio et al 2021, Pfeiffer and Schaub 2023). In contrast, adult survival (0.71) appeared to be lower than expected based on an allometric relationship (Newton et al 2016).…”
Section: Discussionsupporting
confidence: 79%
“…Although breeding has been observed from age two in this species, it is possible that some individuals delay reproduction beyond this age, as observed in other raptors with similar life history traits (e.g. snail kite, Bennetts et al 1998, red kite, Katzenberger et al 2021, Pfeiffer and Schaub 2023), and thus that we may have overestimated reproductive output. We also assumed a breeding probability of 0.9 (Fig.…”
Section: Discussionmentioning
confidence: 77%
“…The detected sensitivity further indicated that the model projections were responsive to these parameters, thereby suggesting potential pathways for conservation measures, for example, highlighting the protection of young individuals and supporting nest success. Pfeiffer and Schaub (2023) reached the same conclusion and identified the breeding output and adult survival as the main demographic drivers when modeling the German red kite population with an integrated population model. Further, their estimates of stage‐wise survival probabilities are in strong agreement with ours.…”
Section: Discussionmentioning
confidence: 66%
“…The red kite (Milvus milvus ) is a widespread European raptor species that has recently recovered from historic persecution in central Europe (Mammen et al 2017, Aebischer andScherler 2021), but is still vulnerable to anthropogenic causes of mortality in south-western Europe (Mateo-Tomás et al 2020, Sergio et al 2021. Despite being a long-lived species with delayed maturity, the temporal fluctuation of productivity was the most important demographic driver of the trajectory of red kite populations (Sergio et al 2021, Pfeiffer andSchaub 2023). A better understanding of the age at which young red kites recruit into the breeding population and contribute to the reproductive output of a population is therefore a key demographic parameter that is so far poorly studied (Katzenberger et al 2021, Literák et al 2022, Pfeiffer and Schaub 2023.…”
Section: Introductionmentioning
confidence: 99%
“…Despite being a long-lived species with delayed maturity, the temporal fluctuation of productivity was the most important demographic driver of the trajectory of red kite populations (Sergio et al 2021, Pfeiffer andSchaub 2023). A better understanding of the age at which young red kites recruit into the breeding population and contribute to the reproductive output of a population is therefore a key demographic parameter that is so far poorly studied (Katzenberger et al 2021, Literák et al 2022, Pfeiffer and Schaub 2023. Developing a tool that allows an objective assessment of this recruitment process would therefore be a useful advance for studying red kite population dynamics.…”
Section: Introductionmentioning
confidence: 99%